Penanaman Akhlakul Karimah pada Siswa Madrasah Ibtidaiyah melalui Pendidikan Agama Islam - Dony Dwi Anggara; Muhammad Nu'man (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2022)
In this research, the type of qualitative research is used and the approach used is library research. The purpose of this study is to provide an education to students and teachers about the importance of Islamic religious subjects (PAI) in the cultivation of morality. The result of this research is that PAI itself is an important thing that needs to be increased its involvement in the curriculum and its implementation. So that it takes a good curriculum design and it is not allowed to make a bad one in the preparation of the PAI curriculum. This is because it is directly related to the formation of good morals for students. If the formation of morality is done poorly, it will also be affected by the character of the students themselves later.